Prevalence of Anemia and Associated Risk Factors among Pregnant Women, What is the Role of Antenatal Care in Prevention? A Cross-sectional Study - Yakar, Burkay; Pirincci, Edibe; Kaya, Mehmet Onur; Onalan, Erhan (Coll Physicians & Surgeons Pakistan, 2021)
Objective: To determine the prevalence of anemia with the associated factors in pregnant women and the effect of medicine practice and antenatal care services provided by family physicians on the prevention of anemia during pregnancy. Study Design: Community-based cross-sectional study. Place and Duration of Study: Family Health Centres in the Elazig region, Turkey from January to June 2019. Methodology: A total of 495 pregnant women, attending the family health centres, were included. Women were administered a questionnaire related with the anemia and related factors; and hemoglobin values were drawn. Hemoglobin concentration <11 g/dl was classified as anaemic. Sociodemographic, individual dietary diversity and obstetric characteristics of the participants were obtained from structured questionnaire form. Binary logistic regression model was employed to determine the effect of explanatory variables on dependent variable anemia. Results: The prevalence of anemia during pregnancy was 27.9% (Hb<11.0 gr/dl). Prevalence of anemia was found lower in participants with higher education levels (p=0.005) and having nutrition education (p=0.004). Income status (OR=0.017 [95%Cl:0.002-0.15, p<0.001]), dark tea preference (OR=87.127 [95%Cl:17.68-429.36, p<0.001]), and iron supplementation time (OR=0.945 [95%Cl: 0.91-0.98, p=0.002]) were determined as the independent predictors of anemia in pregnancy. Conclusion: Low income, insufficient iron supplementation treatment and dark tea preference were the main predictors of anemia. Most of the factors that cause anemia during pregnancy can be prevented with patient education and supportive treatments. Therefore, the authors recommend applying effective and quality prenatal care and patient education programs to reduce anemia during pregnancy.
Keywords: Pregnant women; Anemia; Prenatal care; Family practice; Turkey